Kepemimpinan Dosen Dalam Pembelajaran Daring Di Masa Pandemi Covid 19: Sebuah Kajian Pada Taruna Teknik Penerbangan - Pribadi Asih (Politeknik Penerbangan Indonesia Curug, 2022)
The COVID-19 pandemic, which has spread globally, has resulted in a significant disruption of the world order, encompassing political, economic, social, and educational domains. This study aims to explore the leadership of lecturers in online learning during the Covid 19 pandemic. This study was designed using mixed research both on data collection and data analysis carried out. Primary data collection was carried out by distributing questionnaires to cadets who were selected as respondents. Furthermore, in-depth interviews were conducted with cadet representatives per randomly selected study program. The data obtained will be analyzed using simple statistical equations using a percentage descriptive formula. After obtaining quantitative research results, a triangulation process is then carried out with interview data. The interview was conducted to elaborate the answers on the questionnaire to be carried out a triangulation process based on the concept of lecturer leadership which is the basis of theory. The triangulation process is also carried out by comparing research findings with literature reviews of lecturer leadership in previous studies. The results showed that the leadership of lecturers in online learning during the Covid-19 period was carried out with three criteria, namely conceptual skills, human skills, and technical skills. Based on the results of the questionnaire obtained, it is known that all three have been carried out by lecturers using various tactics in influencing others as an inseparable part of the lecturer's leadership. The leadership style of lecturers, as demonstrated by the three criteria of skills and tactics used in this study to influence others, may serve as a valuable reference for both lecturers at Politeknik Penerbangan Indonesia Curug and those at other universities.